2021
DOI: 10.21519/0234-2758-2021-37-4-65-77
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Criteria for Assessing Protective Immunity at Different Times of Experimental Tularemia in a Mouse Model

Abstract: It is known that the body's defense against infection by the intracellular bacterium Francisella tularensis is provided by the activation of the cellular and humoral immune response. However, their role in long-term protection (25 years and more) against virulent strains of F. tularensis is not well understood. The identification of clear criteria for assessing protective immunity to the tularemia causative agent at different times after vaccination will make it possible to more efficiently develop new genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…In our earlier study, we demonstrated that the long-term protective immunity against tularemia in vaccinated mice depends on the subspecies infecting strain: infection with the virulent F. tularensis 503 of the same holarctica subspecies as the vaccine strain F. tularensis 15 NIIEG provides 100 % protection for 180 days after vaccination; infection with the virulent F. tularensis Schu subspecies of tularensis leads to a decrease in protection with an increase in the postvaccination period to 60 days [4].…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…In our earlier study, we demonstrated that the long-term protective immunity against tularemia in vaccinated mice depends on the subspecies infecting strain: infection with the virulent F. tularensis 503 of the same holarctica subspecies as the vaccine strain F. tularensis 15 NIIEG provides 100 % protection for 180 days after vaccination; infection with the virulent F. tularensis Schu subspecies of tularensis leads to a decrease in protection with an increase in the postvaccination period to 60 days [4].…”
Section: Resultsmentioning
confidence: 95%
“…The obtained data on the significant functional activity of T CM and T EM CD4 + memory T cells at all post-vaccination times explain the mechanism of protection up to 90 days after vaccination of mice who have been infected with the virulent strain F. tularensis 503 subsp. holarctica [4]. In turn, the decreased of functional activity of the T CM and T EM CD8 + memory T cells is correlated with the weakening of protection against virulent F. tularensis Schu subsp.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations